Pharmacognostical and Phytochemical Analysis of Rasayana Churna Vati for Quality Control - An Ayurveda Formulation (International Journal of Ayurveda and Pharma Research, 2021)
Rasayana churna was mentioned by Acharya Vagbhatta for rejuvenation of body tissue. Rasayana properties of this combination revitalize the unhealthy tissue on systemic level. Rasayana Churna is a polyherbal formulation contacting 3 ingredients i.e., Amalaki, Guduchi and Gokshura are well known drugs for its rich in antioxidant, immunomodulator and purifactory action. Repeated stress injury in visual system is major cause of Computer Vision Syndrome- a new milliner disorder. A study conducted as randomized clinical trial showed that Rasayan churana significantly improves a group of symptoms in Computer Vision Syndrome.The present study was carried out to standardize the finished product of Rasayana Churna Vati. It includes Authentication, Organoleptic properties, physic-chemical parameters, assay of active and qualitative HPTLC analysis to confirm entity, quality and purity. All results were compared with Ayurvedic Pharmacopoeial standard. The presence of rosette crystals of calcium oxalate, lignified tissues, prismatic crystals, reticulate vessels, starch grains oval, tannins, trichomes were the characteristic features observed in the microscopy of the prepared drug. Phyto-chemical analysis showed Loss on drying 1.87% w/w, Total ash 4.35% w/w, water soluble extract 34.73% w/w, Acid insoluble ash 0.73% w/w, Alcohol soluble extractive 14.34% w/w & pH 3.4. Identification of constituents of Rasayana Churna Vati was done by HPTLC scanning at 254 and 366mm gives positive test for Guduchi, Gokshura and Amalaki.